Does social interaction make bad policies even worse? Evidence from renewable energy subsidies - Justus Inhoffen; Christoph Siemroth; Philipp Zahn (University of Mannheim, Department of Economics, 2016)
Minimum prices above the market level can lead to ineffcient production and oversupply. We investigate whether this effect is even more pronounced when decision makers are influenced by their social environment. Using data of minimum prices for renewable energy production in Germany, we analyze if individual decisions to install solar panels are affected by the investment decisions of others. We implement a propensity score matching routine on municipality level and estimate that existing panels in the municipality increase the probability and number of further installations considerably, even in areas with minimal solar potential. This social effect is stronger in areas with more solar potential and less unemployment. A higher number of existing panels and more concentrated installations increase the social effect further. We discuss policy implications of these social effects.
urn:nbn:de:bsz:180-madoc-409776
Keywords: H23; L14; Q42; Q48; Q58; 330; EEG; Minimum Prices; Peer Effects; Public Policy; Renewable Energy; Social Interaction; Social Effect; Social Multiplier; Solar Power; Solar Panels; Subsidy